Adverse birth outcomes and associated factors among newborns delivered in Sao Tome & Principe - Vasconcelos, Alexandra (2023)
Publisher Copyright: Copyright: © 2023 Vasconcelos et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.